The COVID-19 pandemic and the gender gap in newly created domains of household labor - Abromaviciute, Jurgita; Carian, Emily K. (Sociological Perspectives, 2022)
In this study, we draw on interview data from 62 matched different-sex, dual-career spouses raising young children to examine the mechanisms behind the gender gap in household labor during the COVID-19 pandemic. We argue that the pandemic represents a unique case of social uncertainty and an opportunity to observe how structural conditions shape the gendered division of household labor. We find that under the rapid social transformation imposed by the pandemic, gender serves as an anchor and orienting frame for couples with young children. We argue that the pandemic (1) expanded traditional gender expectations to new domains of household labor and (2) heightened the importance of gendered explanations for the division of labor that justified intra-couple inequality. Our findings suggest that the particular structural conditions that characterize different times of uncertainty work through slightly different mechanisms, yet produce the same outcome: gender inequality, with long-lasting and wide-ranging implications. © The Author(s) 2022.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; care; charge mentale; conciliation famille-travail; discipline; division sexuelle du travail; famille; inégalités; projet charge mentale; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique; états-unis

“I have no room of my own”: COVID-19 pandemic and work-from-home through a gender lens - Chauhan, Priyanshi (Gender Issues, 2022)
Working from home is not gender neutral. As the COVID-19 pandemic has relocated all non-essential work to the home setting, it becomes imperative to examine the phenomenon through a gender lens. Accordingly, I conducted a qualitative study using semi-structured interviews with 30 dual-earning married couples in India to study the gendered work-from-home experiences of men and women during the pandemic. The findings suggest that the pandemic has disproportionately increased the burden of unpaid work for women as compared to men. Women are negotiating gendered time–space arrangements within their households with the allocation of limited resources being in favor of men. When this interacts with work, gender inequalities are reinforced both at work and home. Gender roles and unpaid work determine women’s choices regarding when and where to work, boundary management between work and non-work domains, and their experiences of social isolation. Further, gender roles have also affected women’s decisions regarding returning to work post-pandemic, where some women may not be returning to work at all. Finally, the paper identifies how gender intersects with the existing conceptual frameworks of working from home, and makes a strong case for integrating gender considerations in the work-from-home policies. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; conciliation famille-travail; covid-19; famille; hétérosexisme; inde; inégalités; inégalités hommes-femmes; pandémie; projet charge mentale; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; travail; travail gratuit